Peningkatan Kesejahteraan Masyarakat melalui Pemberdayaan UMKM untuk Ketahanan Nasional (Kesejahteraan Masyarakat, UMKM, Ketahanan Nasional) - Ghany K.M.R., Muhammad Dliyaulhaq; Thamrin, Suyono; Haetami (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The economic situation now in Indonesia is experiencing weakness due to the impact of the Covid-19 pandemic outbreak. The people at that time were restricted in all their movements to travel, to manage business and so on. So that, it causes the economy of the community and the country declines. For this reason, it is necessary to make efforts made by the government to boost the country's economy. One of them is empowering MSMEs in society. MSMEs are micro, small and medium enterprises that can be used to reduce unemployment, improve the economy in society and overcome poverty. The method used in writing this articles relates to the dialectic of descriptive-qualitative research through library research. The result of this article shows that MSMEs are a good way to improve social welfare and assist in gaining a good national security. Due to a prosperous society, the country's economy will be safe and grows fast, making the country developed country in all aspects. Keywords: Welfare, MSMEs and National Resilience.